Systemic Lupus Erytomatosa in Pregnancy Accompained by Angioedema : A Case Report - Hakim, Masyhur; Debrina Kusuma Devi (Journal of Diverse Medical Research: Medicosphere, 2025)
Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease with diverse clinical manifestations, variable disease progression, and prognosis. SLE is associated with genetic, hormonal, immunological, and environmental factors. Its prevalence in the general population ranges from twenty to one hundred fifty cases per one hundred thousand people. SLE is more commonly found in women, particularly those of reproductive age. Angioedema in SLE patients is a rare occurrence both regionally and globally. scale. This article reports the case of a 24-year-old woman who came to the Emergency Department of Ploso Hospital with complaints of reddish spots on the face area accompanied by swollen lips since 1 week before admission. The patient also complained of a rash on both palms, mouth ulcers on the lips, and hair loss. The patient is currently pregnant with a gestational age of 6 months. Complaints of rashes on the face and swollen lips have been experienced by the patient before. The results of physical examination and support showed that the patient was diagnosed with SLE. This article aims to add insight into cases of angioedema in SLE patients with pregnancy so that further research and development can be carried out.